Use of Drug-level Testing and Single-genome Sequencing to Unravel a Case of Human Immunodeficiency Virus Seroconversion on Pre-exposure Prophylaxis. (20th July 2020) - Spinelli, Matthew A; Lowery, Brentton; Shuford, Jennifer A; Spindler, Jon; Kearney, Mary F; McFarlane, Jenny R; McDonald, Cheryl; Okochi, Hideaki; Phung, Nhi; Kuncze, Karen; Jee, Kathryn; Johannessen, DeeJay; et al.
Abstract: Cases of seroconversion on pre-exposure prophylaxis (PrEP) should be carefully investigated, given their public health implications and rarity. We report a case of transmitted drug resistance causing seroconversion on PrEP in spite of high adherence, confirmed with dried blood spot and segmental hair drug-level testing and single-genome sequencing.